2016
DOI: 10.1002/dta.1971
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of xenon and krypton in equine plasma by gas chromatography‐tandem mass spectrometry for doping control

Abstract: Xenon can activate the hypoxia-inducible factors (HIFs). As such, it has been allegedly used in human sports for increasing erythropoiesis. Krypton, another noble gas with reported narcosis effect, can also be expected to be a potential and less expensive erythropoiesis stimulating agent. This has raised concern about the misuse of noble gases as doping agents in equine sports. The aim of the present study is to establish a method for the simultaneous detection of xenon and krypton in equine plasma for the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Almost simultaneously, Kwok et al reported a quantitative GC/MS headspace analytical method for assay of xenon and krypton in equine plasma for the same purpose . They used a PLOT molecular sieve column for GC separation of gases, as we did.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Almost simultaneously, Kwok et al reported a quantitative GC/MS headspace analytical method for assay of xenon and krypton in equine plasma for the same purpose . They used a PLOT molecular sieve column for GC separation of gases, as we did.…”
Section: Discussionmentioning
confidence: 87%
“…Almost simultaneously, Kwok et al reported a quantitative GC/MS headspace analytical method for assay of xenon and krypton in equine plasma for the same purpose. [35] They used a PLOT molecular sieve column for GC separation of gases, as we did. They employed the method of Goto et al [27] to saturate plasma with xenon and krypton, using the published solubility values to assign gas concentrations to standard plasma dilutions.…”
Section: Discussionmentioning
confidence: 99%
“…LODs for xenon and krypton were 19 pmol/mL and 98 pmol/mL, respectively. [50] Designer drugs in equine doping (Designer) anabolic steroids Designer steroids are considered chemical structures that originally appeared as imitations of endogenous steroids and later as minor modifications of previously marketed products, with the core intention to be undetectable from the current targeted mass spectrometric procedures. To evade detection, the designer steroids have been synthesized to be marketed freely on the Internet, as their structures do not fall within the scope of known steroid structures/biological activities and thus remain uncontrolled by the legal authorities.…”
Section: Nickelmentioning
confidence: 99%
“…Beyond the steroid and GH axes, the experience of racing laboratories over recent years with potential integrity issues surrounding manipulation of the hypoxia inducible factor‐1α (HIF‐1α) axis may suggest that biomarkers capable of identifying such augmentation will be investigated for inclusion in an EBP. Further to the potential misuse of myo ‐inositol trispyrophosphate and cobalt as HIF‐1α stabilizers or noble gases as HIF‐1α activators, a plethora of small‐molecule drug candidates are being investigated to alter HIF‐1α that ‘target’ testing will unlikely keep pace with . Therefore, indirect measures of HIF‐1α manipulation will be vital to any proactive anti‐doping strategy.…”
Section: An Equine Biological Passport (Ebp) For Racingmentioning
confidence: 99%
“…Beyond the steroid and GH axes, the experience of racing laboratories over recent years with potential integrity issues surrounding manipulation of the hypoxia inducible factor-1α (HIF-1α) axis may suggest that biomarkers capable of identifying such augmentation will be investigated for inclusion in an EBP. Further to the potential misuse of myo-inositol trispyrophosphate [69] and cobalt [39,40] as HIF-1α stabilizers or noble gases [70] as HIF-1α…”
Section: Novel Biomarkersmentioning
confidence: 99%